A Literature Review of Emotion Regulation in the Works of Classical Islamic Scholars: Practical Insights from a Spiritual-Ethical Tradition - Mahnoor Saif; Dr Zill-e- Huma; Dr Amina Obaid Khawaja (Al Manhal Research Journal, 2025)
This article provides a theoretical overview of emotion regulation as presented in the works of three influential classical Islamic scholars: Al-Balkhi, Al-Ghazali, and Ibn Khaldun. extracted from their original work and interpretations within Islamic intellectual tradition, the study analyze how each scholar conceptualized emotional processes, self-regulation, and psychological balance in light of faith, reason, and moral development. By situating their insights, the article highlights the convergence between classical Islamic thought and contemporary understandings of emotional well-being. Core themes such as cognitive reframing (Al-Balkhi), spiritual purification and control of the nafs (Al-Ghazali), and the psychosocial influence of environment and education (Ibn Khaldun) are examined to extract relevant, applicable principles for today’s self-help and therapeutic models. This literature-based analysis underscores the richness of Islamic intellectual heritage in addressing emotional challenges and offers pathways for integrating classical wisdom into modern psychological discourse. The article aims to bridge historical perspectives and contemporary needs, contributing to both Islamic psychology and global emotion regulation research.